Innovation and Business Feasibility Analysis of Banana Flavored Spinach Chlorophyll Functional Drink “Dally” - Adi Permadi (Indonesian Journal of Chemical Engineering, 2023)
Indonesia is rich in food sources with bioactive components that have the potential to be developed. Both market research and academic research have shown an increase in consumer awareness and interest in health and nutrition. The prospect of functional drinks one of them can be said to be very promising and profitable. Dally, a functional drink containing spinach essence and banana peel fiber has valuable nutrients such as chlorophyll content (0.2094%), calcium (0.0159%), vitamin C (5,9705 mg/100g), total sugar (1.7334%), and antioxidant IC50 (4077,156 ppm). This drink has a pH of 4.19 and a water activity of 0.955. Based on organoleptic tests on 23 students, it was found that 100% of respondents (liked the taste of Dally, and 65.2% liked the colour and 39% liked the aroma. Market research shows a very high trend for the Yogyakarta and Central Java regions. A SWOT analysis shows Dally has a good chance of being marketed. Meanwhile, Dally's marketing and promotion is carried out through marketplaces such as Shopee, Tokopedia, Facebook and Instagram. Marketing is also carried out with personal selling techniques by visiting potential buyers who are engaged in selling functional drinks. From the calculation, it is known that the cost of goods sold is 7,500 rupiah with a profit margin set of 125%.